Finestkind [videorecording (DVD)] - Helgeland, Brian; Foster, Ben, 1980-; Ortega, Jenna; Wallace, Toby, 1996-; Jones, Tommy Lee, 1946- (Paramount, 2024)
Set in New Bedford, Mass., America's biggest commercial fishing port, FINESTKIND tells the story of two brothers from opposite sides of the tracks, who are reunited as adults over one fateful summer. When desperate circumstances force them to strike a deal with a dangerous Boston crime syndicate, a young woman finds herself caught in the middle. Along the way, sacrifices must be made, and bonds between brothers, friends, and a father and his son are put to the test.